2007
DOI: 10.1159/000099135
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Clinically Significant Microembolism after Carotid Endarterectomy

Abstract: Purpose: Post-operatively detected transcranial Doppler (TCD) embolic signals (ES) are associated with an increased risk of carotid endarterectomy (CEA) stroke/TIA. The aims here were to quantify this risk and determine the most efficient monitoring protocol. Methods: Sequential patients undergoing CEA (enrolled in a randomised, blinded, placebo-controlled trial of peri-operative dextran therapy) had 30-min TCD monitoring in the first post-operative hour. 30-min monitoring was also performed 2–3, 4–6 and 24–36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
1
22
0
1
Order By: Relevance
“…Eight studies, with a total of 1414 individual patients, reported stroke or TIA as an outcome along with data for TCD recording of microembolic signals with high MES counts defined as positive (13,(17)(18)(19)21,32,33,35). The sensitivity and specificity were 52.…”
Section: Stroke or Tia High Mes Countmentioning
confidence: 99%
“…Eight studies, with a total of 1414 individual patients, reported stroke or TIA as an outcome along with data for TCD recording of microembolic signals with high MES counts defined as positive (13,(17)(18)(19)21,32,33,35). The sensitivity and specificity were 52.…”
Section: Stroke or Tia High Mes Countmentioning
confidence: 99%
“…1 These deficits may also occur secondary to postoperative generation of emboli from the surgical site. 2 Intraoperative assessment of the middle cerebral artery (MCA) with transcranial Doppler (TCD) allows online surveillance of hemodynamic changes and can detect passage of cerebral microemboli. 1 Microembolic signals (MES) on intraoperative TCD monitoring are detected in more than 90% of patients undergoing CEA.…”
mentioning
confidence: 99%
“…3,5 Although the highest number of MES occurs during declamping of the ICA, detection of MES during dissection of the carotid arteries or during the first postoperative hour correlates with the development of new ischemic lesions on postoperative diffusion-weighted MRI (DWI) or new neurological deficits immediately after CEA. 2,3,5 The target vessel is not opened during dissection, and, thus, all detectable MES are solid. 3 Furthermore, during this stage of the procedure, the fragile plaque, a source of emboli, has not yet been removed and is still exposed to blood flow.…”
mentioning
confidence: 99%
See 2 more Smart Citations